A circularly polarized tunable frequency circular patch antenna for S-band space base application - Waranon, Likhit; Dentri, Sitthichai; Phakphisut, Watid; Krairiksh, Monai; Phongcharoenpanich, Chuwong (My University, 2025)
This research proposes a unidirectional circularly polarized tunable frequency circular patch antenna scheme for S-band uplink satellite communications. In the antenna scheme, the circular radiating patch is enclosed by 4×8 rectangular-shaped auxiliary elements along the +x, −x, +y, and −y−axes. To shift the resonant frequency of the antenna to lower frequencies, the auxiliary elements on the four axes are uniformly shorted. There are nine shorting configurations (configurations A – I) corresponding to the S-band uplink chain (2.025 GHz to 2.110 GHz). Besides, the circular polarization is switchable between right- (RHCP) and left-hand circular polarization (LHCP) by relocating the feed point from the +y axis for RHCP to +x axis for LHCP. Switching mechanisms dynamically reconfigure the antenna by modifying its electrical length to support multiple frequency bands, all of which maintain circular polarization. Since the proposed antenna scheme is intended for the S-band uplink frequency of 2.06 GHz, measurements are carried out with configuration F of the antenna scheme. The measured impedance bandwidth (|S11|≤-10 dB) and axial ratio bandwidth (AR<3 dB) are 6.2% and 4.49%, with the maximum gain of 6.54 dBic for RHCP and LHCP. The radiation pattern is of unidirectionality. Furthermore, the proposed antenna scheme meets the qualification sine vibration and random vibration test requirements. The proposed antenna scheme is thus suitable for S-band uplink satellite communications. The novelty of this research lies in the use of the auxiliary elements of various shorting configurations to achieve frequency tunability; and the alteration of the feed point location to switch between RHCP and LHCP.
Keywords: Patch antenna; Satellite antenna; Satellite communication; Space environment; Tunable antenna